Pediatric Disaster Triage System - Gülşen YALÇIN; Murat ANIL (Forbes Tıp Dergisi, 2022)
It is important to be aware of and prepare for the possible consequences of disasters. In the event of any disaster, disaster triage is to do what is most beneficial for the large number of injured by using the limited resources. After the disaster, the injured victims are classified according to their injury status with an effective and fast triage. When available resources are used optimally under triage guidance, mortality and morbidity are reduced. Every country must have a disaster management plan. Children's anatomical and physiological characteristics are different from adults and they are vulnerable to disasters. Although one-third of the disaster victims were children, pediatric issues were not adequately addressed in the planning. In this article, it is aimed to provide information about the triage systems determined and accepted to be used for child victims aged 0-8 in disasters.